Absorption and secretion of water and electrolytes by the intact human colon in diffuse untreated proctocolitis. Issue 1 (January 1970) - Harris, J.; Shields, R.
Abstract : The net transport and unidirectional fluxes of water, sodium, and potassium were studied in four subjects with diffuse untreated proctocolitis, by perfusing the colon with isotopically-labelled solution instilled through a tube introduced by mouth. The results were compared to those obtained in 13 healthy subjects. In proctocolitis the colonic absorption of sodium and water was impaired and the secretion of potassium increased. The movement of electrolytes across the colonic mucosa into the lumen was increased and the movement in the opposite direction reduced. The close correlation between water and sodium absorption in healthy subjects was maintained in those with proctocolitis. These alterations in the colonic handling of water and electrolytes diminish the reserve capacity of the colon and may explain the diarrhoea of proctocolitis.